Peran Mahasiswa MBKM Mandiri dalam Kegiatan P5 Siswa Kelas XI di SMAK Giovanni Kupang Tahun Pelajaran 2024/2025 - Febrianus Borkonda Tanis; Natalia Twignarti Alfilia Nanga; Archangela Chriani Mbeo Bai; Margaretha Mbere Cherista; Skolastika Gae Nua; Kristinus Sembiring (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze the role of independent Merdeka Belajar Kampus Merdeka (MBKM) students in the implementation of the Project to Strengthen the Pancasila Student Profile (P5) for grade 11 students at SMAK Giovanni Kupang in the 2024/2025 academic year. The results of the study show that the involvement of MBKM students has a significant impact on the success of P5 activities. MBKM students act as facilitators, peer tutors, and sources of knowledge that enrich student learning. Their presence helps students understand abstract concepts, develop soft skills, and increase motivation to learn. Overall, the collaboration between students, teachers, and MBKM students in P5 activities has created a more dynamic and effective learning environment.